A comparison of two imaging modalities for detecting lymphatic nodal spread in radiochemotherapy of locally advanced cervical cancer. (October 2018) - Waldenström, Ann-Charlotte; Bergmark, Karin; Michanek, Annika; Hashimi, Farida; Norrlund, Rauni Rossi; Olsson, Caroline E.; Gjertsson, Peter; Leonhardt, Henrik
Abstract: Background and purpose: In uterine cervical cancer tumour spread reaching the para-aortic lymph nodes is the most significant independent pre-treatment predictor of progression-free survival. When introducing [ 18 F]fluorodeoxyglucose-positron emission tomography (FDG-PET)/computed tomography (CT) in our clinic for patients with advanced cervical cancer planned for definitive radiochemotherapy, the purpose of this study was to quantify to what extent the added information lead to changes in radiotherapy planning. Material and methods: We included 25 consecutive patients with cervical cancer stages IB2 – IIIB planned for definitive radiochemotherapy between November 2010 and May 2012. The patients were examined both with magnetic resonance imaging (MRI) and FDG-PET/CT before treatment and after four weeks of treatment. Results: In 11/24 (46%) of the patients the FDG-PET/CT before treatment provided additional diagnostic information leading to changes in treatment planning compared to information from MRI. Seven of these eleven patients (64%) were alive and without evidence of disease at four-year follow-up. The MRI detected pelvic tumour spread not seen on the FDG-PET/CT in 2/24 patients. The disease-free four-year survival was 59%. Conclusions: Additional diagnostic information from FDG-PET/CT changed treatment strategy in almost half of the patients and may have increased chances of survival in this limited group of patients with locally advanced uterine cervical cancer. We recommend both modalities for nodal detection.